Higher Education Institutions and International Students’ Hindrances: A Case of Students From the African Portuguese-Speaking Countries at Two European Portuguese Universities - Ambrósio, Susana; Marques, João Filipe; Santos, Lucília; Doutor, Catarina (Journal of International Students, 2017)
We present a study to comprehend if the support given by higher education institution (HEI) to international students coming from the PortugueseSpeaking African Countries meets their academic and social hindrances. Our starting point was a set of semi-structured interviews focused on the perspectives of these students, their Professors and Course Directors as well as on the perspectives of HEI’ staff. Despite findings indicate a positive institutional support, it seems there is still much to do in order to do it properly with these students. These different perspectives will allow us to reflect on the impact that those actions/resources have on the path of students from Portuguese-Speaking African Countries and to systematize suggestions to enhance their experiences in HE.